BALF editome profiling reveals A-to-I RNA editing associated with severity and complications of Mycoplasma pneumoniae pneumonia in children - Yun-Yun Jin; Yun Guo; Su-Wan Xiong; Na Zhang; Jian-Huan Chen; Feng Liu (mSphere)
ABSTRACT Mycoplasma pneumoniae is an important human respiratory pathogen that causes mild-to-moderate community-acquired M. pneumoniae pneumonia (MPP), particularly in children. RNA editing plays a vital role in pathogen infection and host immune response, but it remains largely unknown how it could be involved in the epigenetic regulation of host response to M. pneumoniae infection. In the present study, we performed an epitranscriptomic analysis of adenosine to inosine (A-to-I) editing in 39 bronchoalveolar lavage fluid (BALF) samples from the severe side (SS) and the opposite side (OS) of patients with MPP. Our editome profiling identified 87 differential RNA editing (DRE) events in 50 genes, especially missense editing events that recoded C-C motif chemokine receptor-like 2 (CCRL2, p.K147R) and cyclin I (CCNI, p.R75G). The expression of adenosine deaminase acting on RNA (ADAR) significantly increased on SS compared to OS and positively correlated with the average RNA editing level and individual DRE events. Meanwhile, functional enrichment analysis showed that DRE was observed in genes primarily associated with the negative regulation of innate immune response, type I interferon production, and cytokine production. Further comparison of SS between complicated MPP (CMPP) and non-complicated MPP (NCMPP) revealed RNA editing events associated with MPP complications, with a higher ADAR expression in CMPP than NCMPP. By identifying DRE events as biomarkers associated with MPP severity and complications, our editome profiling provides new insight into the potential role played by A-to-I RNA editing in modulating the host’s immune system during M. pneumoniae infection.IMPORTANCEOur research investigates how Mycoplasma pneumoniae, a common respiratory pathogen, influences how our cells modify their genetic instructions. By studying RNA editing changes in bronchoalveolar lavage fluid from patients with M. pneumoniae pneumonia, we aim to investigate how M. pneumoniae infection alters epigenetics and contributes to the disease severity and complications. Understanding such epigenetic alterations not only sheds light on the mechanisms underlying M. pneumoniae infection but also holds potential implications for developing better diagnostic tools and therapies. Ultimately, this work may facilitate the design of more targeted treatments to alleviate the impact of respiratory infections caused by the pathogen. Our findings may also offer broader insights into how microbial infections reshape immune processes, highlighting the importance of RNA editing in host-pathogen interactions.